Desain Sensor Kelembapan Relatif Udara Menggunakan Fiber Optik - Rangga Pradana Wahyudi; Yoyok Heru; Mila Kusumarwadani (Politeknik Negeri Malang, 2021)
Air humidity is an important factor in human life, namely to maintain body health stability which will also affect work comfort. A sensor is needed to know the humidity in the room. A tool can be said to be a sensor if it has linearity and sensitivity, in this case optical fiber is suitable for sensors due to its natural ability to be resistant to electromagnetic interference, resistant to high temperatures, has high sensitivity and flexibility, and can be used for measurement and remote sensing. This study uses 2 singlemode SC-SC core patch cables connected to a fiber coupler that has been given a hole in the middle with a diameter of 1mm and the ferulle spacing is 0.3mm, 0.6mm, 0.8mm, 1mm. Optical light source is used to provide input with a value of -7dBm and the output value will be read by the Optical power meter which will later be processed into power loss then compared with the value from the Hygrometer and will obtain a linear equation. The measurement results, it is found that the farther the distance between the ferules, the longer the range obtained. The longest range is obtained at a distance measurement of 1mm with a power loss difference of 0.2dB and the shortest range is obtained at a measurement of 0.3mm with a power loss difference of 0.08dB.